(untitled) (Journal of Applied Learning and Teaching, 2022)
Teaching and learning mathematics in Malawi primary schools has been of concern for many years. This is because of the low learner achievement in national assessments by the Malawi National Examinations Board, where learners’ performance in mathematics at end of primary education has been consistently low. In other assessments, such as the Early Grade Mathematics Assessment (Brombacher, 2011) and the numeracy assessment by the Southern and Eastern Africa Consortium for Monitoring Education Quality (SACMEQ, 2011), the average performance of Malawi learners has been below the expectation of the curriculum. In an attempt to address the issues and improve the quality of teaching and learning of mathematics, there have been curriculum reforms which revised the content objective based curriculum to learner outcome based curriculum and aimed at shifting teaching from traditional teacher centred to more learner centred teaching approaches (Ministry of Education, 2007). In addition, over the years there have been interventions in the teaching and learning of mathematics; some interventions targeted mathematics teachers in schools to implement new teaching strategies, while other interventions targeted entire schools and communities. In this paper, we review the reforms and interventions, analyse their successes and challenges, and discuss the implications for improving the teaching and learning mathematics in Malawi primary schools.